2005
DOI: 10.1128/jvi.79.16.10308-10329.2005
|View full text |Cite
|
Sign up to set email alerts
|

ERK1/2 and MEK1/2 Induced by Kaposi's Sarcoma-Associated Herpesvirus (Human Herpesvirus 8) Early during Infection of Target Cells Are Essential for Expression of Viral Genes and for Establishment of Infection

Abstract: Kaposi's sarcoma-associated herpesvirus (KSHV) in vitro targetKaposi's sarcoma-associated herpesvirus (KSHV), a member of the lymphotropic human gamma-2 herpesvirus family (genus Rhadinovirus) (45, 50) is etiologically linked with Kaposi's sarcoma (KS), a multifocal endothelial cell tumor most commonly seen in AIDS patients (14). KS lesions are characterized by the presence of spindle-shaped endothelial cells and inflammatory cells. Several lines of evidence point to a central role of KSHV in the pathogenesis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

16
244
1
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 162 publications
(262 citation statements)
references
References 71 publications
16
244
1
1
Order By: Relevance
“…Since Erk-activation could be inhibited by HNMPA, our data further suggest that Erk activation in latently infected cells is largely due to activation of the IR. In addition, it has been shown that the Erk pathway is activated by KSHV during de novo infection to modulate initial gene cellular and viral expression (Sharma-Walia et al, 2005). PI3K is also activated early in KSHV infection (Sharma-Walia et al, 2005), while we did not see PI3K activation in latently infected cells since there was no change in AKT phosphorylation in KSHV infected E-DMVEC (Figure 7).…”
Section: Discussionmentioning
confidence: 68%
“…Since Erk-activation could be inhibited by HNMPA, our data further suggest that Erk activation in latently infected cells is largely due to activation of the IR. In addition, it has been shown that the Erk pathway is activated by KSHV during de novo infection to modulate initial gene cellular and viral expression (Sharma-Walia et al, 2005). PI3K is also activated early in KSHV infection (Sharma-Walia et al, 2005), while we did not see PI3K activation in latently infected cells since there was no change in AKT phosphorylation in KSHV infected E-DMVEC (Figure 7).…”
Section: Discussionmentioning
confidence: 68%
“…Structural analysis of purified virions of other herpesviruses, including HSV, CMV, EBV, and rhesus rhadinovirus, indicate that the conserved protein kinases of these viruses are also incorporated into mature virus particles (2,12,37,50,52). This finding suggests that this kinase may play a role in phosphorylating viral proteins during virion assembly and/or regulate the functions of viral and cellular proteins upon entry into host cells and during the early stage of de novo infection (47).…”
Section: Discussionmentioning
confidence: 78%
“…3C; upper panel), which indicated that the exogenously transfected mir-143 precursor miRNAs caused the decreased expression of the ERK5 protein at the translational level. The level of c-myc protein, a downstream signal protein of ERK5 (13,14), was also reduced after the transfection ( Fig. 3C; lower panel).…”
Section: Resultsmentioning
confidence: 89%
“…Thus, in the case of the signal molecules in the MAPK system and transcription factors targeted by such an miRNA, the expression of many proteins would be affected, leading to deregulation of the signal transduction of cell growth, survival and death. c-myc is also lowered by the transfection of cells with mir-143 precursor miRNAs, perhaps due to the decreased expression of ERK5, because c-myc lies downstream of the cell growth signaling pathway including ERK5 (13,14).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation